The Combination of Particle Irradiation With the Hedgehog Inhibitor GANT61 Differently Modulates the Radiosensitivity and Migration of Cancer Cells Compared to X-Ray Irradiation - Konings, Katrien; Vandevoorde, Charlot; Belmans, Niels; Vermeesen, Randy; Baselet, Bjorn; Walleghem, Merel Van; Janssen, Ann; Isebaert, Sofie; Baatout, Sarah; Haustermans, Karin; Moreels, Marjan (Frontiers in Oncology, 2019)
Due to the advantages of charged particles compared to conventional radiotherapy, a vast increase is noted in the use of particle therapy in the clinic. These advantages include an improved dose deposition and increased biological effectiveness. Metastasis is still an important cause of mortality in cancer patients and evidence has shown that conventional radiotherapy can increase the formation of metastasizing cells. An important pathway involved in the process of metastasis is the Hedgehog (Hh) signaling pathway. Recent studies have demonstrated that activation of the Hh pathway, in response to X-rays, can lead to radioresistance and increased migratory and invasive capabilities of cancer cells. Here, we investigated the effect of X-rays, protons and carbon ions on cell survival, migration and Hh pathway gene expression in prostate cancer (PC3) and medulloblastoma (DAOY) cell lines. In addition, the potential modulation of cell survival and migration by the Hh pathway inhibitor GANT61 was investigated. We found that in both cell lines, carbon ions were more effective in decreasing cell survival and migration as well as inducing more significant alterations in the Hh pathway genes compared to X-rays or protons. In addition, we show here for the first time that the Hh inhibitor GANT61 is able to sensitize DAOY medulloblastoma cells to particle radiation (proton and carbon ion) but not to conventional X-rays. This important finding demonstrates that the results of combination treatment strategies with X-ray radiotherapy cannot be automatically extrapolated to particle therapy and should be investigated separately. In conclusion, combining GANT61 with particle radiation could offer a benefit for specific cancer types with regard to cancer cell survival as well as migration.